Maverick Mothers and Mercy Flights: Canada’s Controversial Introduction to International Adoption - Brookfield, Tarah (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2008)
AbstractIn the 1970s, two private adoption agencies faced state and public scrutiny over their ‘rescue’ of orphans from Bangladesh, Vietnam and Cambodia. The organizations were run by four Canadian mothers who themselves adopted over fifty children and placed hundreds more with other Canadian families. Inspired by a sense of maternal internationalism, these ‘maverick mothers’ were convinced that removing the children from their war torn nations and bringing them to Canada was in each child’s best interest. According to professional social workers and diplomats, a strong commitment to maternalism and internationalism were not valid enough to trust the complicated operation of international adoption to amateur humanitarians. The mothers’ lack of professional accreditation, their bleeding heart mentality, and examples of radical behavior at home and abroad were seen to threaten international adoption as a legitimate form of child saving. Yet concurrently, the authority and respect granted by the women’s identity as mothers marinated their cause with a certain creditability or at least admiration for their efforts, which gave them a sense of empowerment to challenge and for most of them, to ultimately cooperate with their critics.